2017
DOI: 10.3390/ijms18091883
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitor-Induced Autophagy in Tumor Cells: Implications for p53

Abstract: Autophagy is an essential process of the eukaryotic cell allowing degradation and recycling of dysfunctional cellular components in response to either physiological or pathological changes. Inhibition of autophagy in combination with chemotherapeutic treatment has emerged as a novel approach in cancer treatment leading to cell cycle arrest, differentiation, and apoptosis. Suberoyl hydroxamic acid (SAHA) is a broad-spectrum histone deacetylase inhibitor (HDACi) suppressing family members in multiple HDAC classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 222 publications
(312 reference statements)
4
46
0
Order By: Relevance
“…Our experimental evidence thus underlines an overall major regulatory role for p53 not only in HDACi-mediated apoptosis but also in HDACi-stimulated autophagy (Figure 3) (reviewed in [57,141]). As a consequence, p53-deficiency could moreover explain apoptosis resistance as well predominant induction of HDACi-provoked autophagy in cancer cells.…”
Section: Hdaci-induced Autophagy Mediated By P53supporting
confidence: 58%
See 2 more Smart Citations
“…Our experimental evidence thus underlines an overall major regulatory role for p53 not only in HDACi-mediated apoptosis but also in HDACi-stimulated autophagy (Figure 3) (reviewed in [57,141]). As a consequence, p53-deficiency could moreover explain apoptosis resistance as well predominant induction of HDACi-provoked autophagy in cancer cells.…”
Section: Hdaci-induced Autophagy Mediated By P53supporting
confidence: 58%
“…An impressive diversity of mechanisms have been uncovered in cancer cells that promote HDACi-elicited autophagy which include mostly attenuation of mTOR signaling that can occur in combination combined with increased expression of LC3, Beclin-1, or ATG and can be provoked by endoplasmic reticulum stress (reviewed in [57] and Table 1 [141]). mTOR is a well-known regulator of the canonical pathway of autophagy involving the regulation of the ULK1 complex and Beclin-1.…”
Section: Mechanisms Of Hdaci-induced Autophagic Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial evidence has shown the ability of pan-HDAC inhibitors to promote autophagy [26,27]. During autophagy, the formation of acidic vesicular organelles (AVOs) is one of the characteristic features of cells engaged in autophagy in response to starvation or radiation [28].…”
Section: Hmc Induces Autophagymentioning
confidence: 99%
“…Over the last few years, the link between autophagic process regulation and HDACs or HDAC inhibitor (HDACi) has been gradually noticed (18). Inconsistently, autophagy modulation by HDACs or HDACi was pleiotropic in a cell type-dependent manner (19). For example, in HeLa cells, HDACi FK228 induced autophagic vacuole formation and lysosome function (20), whereas Cao et al (21) found that HDACi trichostatin A (TSA) suppressed autophagic activation and attenuated hypertrophic growth in cultured cardiomyocyte.…”
mentioning
confidence: 99%